Analisis Perbandingan Alternatif Model Peremajaan Kelapa Sawit Konvensional Dengan Underplanting Pola Perkebunan Inti Rakyat (Pir) di Desa Sei Lambu Makmur Kecamatan Tapung Kabupaten Kampar - Eti Susanti; Sakti Hutabarat; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Oil palm (Elaeis guineensis jacq) is one of profitable crops in Riau Province. Oil palm plantations have been cultivated by various type of business including large enterprises and smallholders. Oil palm has been grown by a large number of population in the Province of Riau. In the village of Sei Lambu Makmur, District of Tapung, Regency of Kampar, the oil palm plantation are at the end of the economic life . To maintain sustainable production the oil palm trees should be replanted. There are three alternative replanting models i.e., conventional, underplanting, and conventional with intercropping. Conventional and underplanting are possible models for smallholders and mill. This aim of this research is to analyse the most suitable model for the condition of the smallholders. Primary data was collected by direct interview with oil palm smallholders while secondary data was obtained from relevant agencies. This study analysis the feasibility of the replanting models by using four investment criteria is NPV, IRR , Net B/C and sensitivity analysis. The results show that underplanting is the most suitable model for smallholder. However, the conventional model is the most efficient model from the mill’s point of view. Keyword: oil palm, replanting model, NPV, IRR, sensitivity analysis